Optimization of Electric Vehicles Wireless Charging - Gesrou, Abdalla (2019)
A Master of Science thesis in Mechatronics Engineering by Abdalla Gesrou entitled, “Optimization of Electric Vehicles Wireless Charging”, submitted in December 2019. Thesis advisor is Dr. Ahmed Osman and thesis co-advisor is Dr. Shayok Mukhopadhyay. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).